(3TQM GdCQLhRI GdjGSejfjI aj Yde GdLHQs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3GHf GdjGSejf , YHO Gddg Hf eMeO Hf MLGL, CHh eMeO,J (B601 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh GdaVGFd SHW GdeGQOjfi GdMeO ddg GdPi LHQ bdhH ChdjGFg CeG HYO agPG JYdjb eNJUQ hVYJg TQMkG Ydi GdCQLhRI GdjGSejfjI s
(3BNQgG (B:s
(3aQO cd eSJKfi cd efgeG YdjgG HCf JRjO NeSI CMPGQ Ydi GdCehGd hYdi YOjdgG KeGfjI CehGd cGedI hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf L(B1 (3U` (B62 (3Cf GdCQLhRhI ai GdLHQ hGdebGHdI gi deDdagG CHh YHO Gddg eMeO Hf MLGL GdeYQha HGHf GdjGSejf hGdeJhai SfI (B601 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B124 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B115s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs